Validation and utility of the Attitudes to Ageing Questionnaire: Links to menopause and well-being trajectories. Issue 2 (October 2015) - Brown, Lydia; Bowden, Stephen; Bryant, Christina; Brown, Valerie; Bei, Bei; Gilson, Kim-Michelle; Komiti, Angela; Judd, Fiona
Highlights The World Health Organisation Attitudes to Ageing Questionnaire (AAQ) was validated for use among midlife women. A positive attitude to ageing was found to predict a positive experience of menopause, as measured by low menopausal problem ratings and more adaptive beliefs about menopause. Attitude to ageing was a significant predictor of 10-year well-being trajectories, in that negative age attitudes predicted declines in well-being over time.